Dynamics Simulation Analysis of a New Type of Lightweight Bridge Crane Reducer - Zhu Shuaihua; Liu Zhongming; Zhang Zhihong; Yan Shidang (Jixie chuandong)
Taking one new type crane reducer with two supporting points as the research object,the three-dimensional model of reducer is established by using SolidWorks,and the virtual prototype is established by importing the 3D model into the mechanical dynamics simulation software ADAMS. In order to ensure the accuracy of the simulation model,the virtual prototype model is analyzed by the contact force constraint,the angular velocity characteristic curve and the gear meshing force variation curve of each drive shaft are obtained. The simulation of the actual value and the theoretical calculation results are compared and found that the transmission shaft angular velocity and the actual the transmission error value in 0. 17%,engaging in 4% errors are very small,so the simulation model is correct. The research results provide data support for calculate gear strength and fatigue life more accurately.